The Stranger on the road to emmaus - "Cross, John .R." ("Durham, ON :")
Includes an appendix
Keywords: "BIBLE - CRITICISM, INTERPRERTATION, ETC;CHRISTIANITY - ESSENCE, GENIUS, NATURE;THEOLOGY, DOCTRINE - PECULAR WORKS"